The structural and stratigraphic setting of the Rosh Pinah zinc-lead deposit within the Gariep trough - Alchin, Dennis John (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.